EXPERIMENTAL STUDY OF THE ACID LEACHING PROCESS OF DOLOMITE - Guevara Orozco, Lisandra; Enríquez García, Mixary; Mollineda Trujillo, Ángel; Herrera Álvarez, Suleidys; Santos Herrero, Ronaldo F.; Ley Chong, Néstor (Centro Azúcar Journal, 2025)
Introduction: Magnesium sulfate is crucial for Cuban agriculture and pharmaceutical industry. Its production through acid leaching of dolomite, an abundant resource in Cuba, requires evaluating its fundamental parameters. Objective: To determine the magnesium concentration in magnesium sulfate solutions using the Plackett-Burman design. Materials and Methods: Dolomite from Villa Clara was processed through leaching with H₂SO₄, evaluating acid concentration, temperature, time and agitation according to Plackett-Burman design. Mg²⁺ concentration was measured by atomic absorption spectrometry. Results and Discussion: The magnesium concentration ranged between 680.5 and 987.5 mg/L. The maximum concentration (987.5 mg/L) was obtained with high acid concentration (98%), low temperature (30°C) and high agitation (400 rpm). Conclusions: Acid concentration and agitation speed are the most influential factors in the process. The experimental design proved effective for identifying the conditions that maximize magnesium concentration.